ANALISIS PERUBAHAN SIKAP KENYA TERHADAP ARMS TRADE TREATY - Triutama, Reynaldi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
This research discusses about Kenya policy towards Arms Trade Treaty. Kenya is a victim of the proliferation of illegal weapons, which worsens domestic conflicts. Kenya was part of six ATT sponsor countries, which is Argentina, Australia, Costa Rica, Finland, Japan and the United Kingdom. At the regional level Kenya is incorporated in The Nairobi Protocol which discusses the control, prevention and reduction of illegal weapons with other African countries in the Horn of Africa and the Great Lakes of Africa. But in 2013 when ATT was adopted by the United Nations through a voting channel to become a resolution, Kenya took an anticlimax stance which initially supported and played an active role in the formulation of the resolution changed and choose abstain. This study tried to answer why there was a change from Kenya which initially supported the ATT and actively participated in the formulation of ATT to become passive by not taking action when ATT was adopted as a UN resolution. This study uses the Foreign Policy Decision Making framework described by William Coplin who emphasizes that in decision making in a country there are three determinant factors namely domestic political conditions, economic and military capabilities and an international context that encourages a country to take its foreign policy. This study found the reason for the refusal of the ATT ratification by Kenya was due to Kenya's unpreparedness to adopt ATT into its national law, concerns from Kenyan leaders about the relationship between ATT and the ICC and concerns that ATT could weaken Kenya's military capabilities.